Computing second-order-accurate solutions for rational expectation models using linear solution methods - Giovanni Lombardo; Alan Sutherland (European Central Bank (ECB), 2005)
This paper shows how to compute a second-order accurate solution of a non-linear rational expectation model using algorithms developed for the solution of linear rational expectation models. The result is a state-space representation for the realized values of the variables of the model. This state-space representation can easily be used to compute impulse responses as well as conditional and unconditional forecasts.
Keywords: C63; E0; 330; Second order approximation; Solution method for rational expectation models; Rationale Erwartung; Zustandsraummodell